Modeling the rice production under varied agro ecological situations of Palakkad district and its vulnerability to climate change - Anandu S Hari (Acadamy of Climate Change Education and Research, 2018)
The research project entitled "Modeling the rice production under varied Agro-Ecological Situations of Palakkad district and its vulnerability to climate change". Was carried out at RARS Pattambi and the daily rainfall data for the period 1991-2014 was collected from the India Meteorological Department, Thiruvananthapuram. The weather data from General Circulation Models based on RCP 4.5 and 8.5 were used for the analysis and projections were made up to 2050. Weather cock v.1.5 was used for converting the daily weather data into standard week, month and seasonal formats. The rainfall parameters or indices like seasonal and monthly rainfall, rainy days and high rainfall events were calculated. It is also used to compute PET and Thornthwaite water balances. The crop simulation model DSSAT-developed by IBSNAT was used for studying the impact of climate change on these ecosystems. The monthly rainfall of various Agro ecological units of Palakkad district indicate an increased rainfall during the months June, July and August in Projected climate as per RCP 4.5 a weakening in rainfall can be noticed during the months January, February, September and December in projected climate, annually, the number of rainy days indicates a declining trend in projected climate. In a nut shell, the wet months will be watter and dry periods will be drier. The south west monsoon and summer season shows an increasing tendency in the number of rainy days and amount of rainfall in projected climate. Most of the agro-ecological units in Palakkad district showed a decreasing pattern in the length of growing period in projected climate as per RCP 4.5 In projected climate, the maximum amount of potential evapotranspiration can be observed during the months May, July and September whereas the minimum will be in January, November and December. The yearly potential evapotranspiration shows an increasing trend in projected climate as per RCP 4.5. The number of periods where deficit will happen indicate a decreasing trend whereas the annual amount of deficit shows an increasing pattern in projected climate. As per the projections maximum amount of water deficit will happen during the month March in most of the agro ecological units of central Kerala. Annually the amount of water surplus indicates an increasing trend in projected climate based on RCP 4.5. In RCP 4.5, which is the most likely scenario for India, the yield reduction will be 10 per cent by 2030s and 2050s respectively. It can be observed from the study that the impact of climate change on rice production varied widely under different agro ecological situations. The major rice growing tracts of Palakkad district except Palakkad eastern plains (AEU 23) showed decline in productivity.